Immunoexpression of BAP1, ROS1, and ALK in Spitzoid Melanocytic Tumors. (September 2018) - Cardili, Leonardo; Viana, Cristiano Ribeiro; Germano, Andressa; Fernandes, Mariana; Barcellos, Denise; Landman, Gilles
Background . Spitzoid tumors are a heterogeneous group of melanocytic neoplasms that frequently imposes diagnostic difficulties. Lately, several advances in molecular biology afforded significant discoveries on the pathogenesis of these tumors. BAP1 (BRCA-1 associated protein-1) inactivation and anomalous expression of kinase translocation-related proteins are among the main criteria launched by new classification proposals. Our aim was to systematically assess the immunoexpression of BAP1, ROS1 (receptor tyrosine kinase c-Ros oncogene 1), and ALK (anaplastic lymphoma receptor tyrosine kinase) proteins in an unpublished series of spitzoid tumors. Methods . Retrospective study based on 47 formalin-fixed paraffin-embedded tissue samples from 3 different institutions. BAP1, ROS1, and ALK immunostains were performed in all cases. We included 27 Spitz tumors without significant abnormality, 15 atypical spitzoid tumors, and 5 spitzoid melanomas. Results . We observed loss of BAP1 nuclear immunolabeling in 4.3% of evaluable cases (2/46), both of them atypical spitzoid tumors. The proportional frequency of BAP1-inactivated cases among atypical spitzoid tumors was 14.2% (2/14). No immunoexpression of ROS1 or ALK was found. Conclusions . Our study revealed 2 additional BAP1-inactived cases and described its respective frequency. The absence of anomalous expression of translocation-related proteins ALK and ROS1 in this series, composed predominantly of low-grade/low-risk tumors, indicates that translocated spitzoid lesions may not be as prevalent as initially suggested, at least in some populations. Furthermore, our findings encourage additional investigation on unequal occurrence of such immunomarkers among different diagnostic categories of spitzoid neoplasms.